Analisis Wacana Kritis Pemberitaan Penolakan Tambang Andesit di Desa Wadas pada Tempo.co - Abdi Sri Kuncoro (MediaTor (Jurnal Komunikasi), 2022)
This study explains the dimension of the Teun A van Dijk model in online text news entitled "Rejecting the Andesite Mining in Wadas Village" by Tempo.co. Tempo's online newspaper provided survey data and data sources in text news entitled Rejecting the Andesite Mining in Wadas Village. The data collection technique in this research is used a descriptive-analytical documentation method with a critical discourse analytical approach of the Teun A van Dijk models. Investigation in Teun Van Djik's theory consists of three dimensions. Those three dimensions are superstructure, macrostructure, and microstructure dimensions. The superstructure dimension is about text consistency and schematization. The macro-structural dimension of Van Dijk's critical discourse analysis of the model discusses the problem: the discussion of the inhabitants of the village of Wadas refusing to mine andesite in their area. The microstructure dimension is background, detail, Intent, premise, sentence form (passive and active clauses), coherence (additive/additive coherence, causal coherence, and contrast coherence), pronouns (they and our pronouns), lexicons, graphics, and metaphors.